Modeling water and salt migration in groundwater and vadose zones to assess agricultural sustainability in Karamay Irrigation District - Jiawei Ren; Tongkai Guo; Changyan Tian; Wenxuan Mai; Xiaomin Mao (Agricultural Water Management, 2025)
The agricultural region of Karamay in northern Xinjiang, China, faces serious challenges to agricultural sustainability due to primary salinization, arid climatic conditions and a lack of effective drainage systems. To evaluate the influence of groundwater depth and salinity on soil salinization and analyze the sustainability of agricultural development, this study employed a three-dimensional (3D) water and solute transport model (FEFLOW) to simulate water-salt dynamics in both groundwater and vadose zones across cropland, forest land, and desert. The model was calibrated and validated using 2006–2021 data, showing good agreement with observed groundwater levels (R²=0.70, RMSE=0.27 m), groundwater salinity (R²=0.72, RMSE=2.08 dS/m), and soil salinity (R²=0.71, RMSE=0.56 dS/m). Results demonstrate that during the early stage of irrigation district development (2006–2010), flood irrigation effectively leached salts and mitigated salinization, but also caused a rapid rise in groundwater levels. The subsequent adoption of water-saving irrigation slowed the groundwater rise, but due to its limited leaching capacity and strong evaporation, salt accumulated in the surface soil, intensifying salinization phenomenon. The study reveals that groundwater depth and salinity significantly influence soil salinity distribution, with agricultural development playing a critical role in regional water-salt dynamics. Scenario simulations for 2022–2030 indicate continued groundwater rise to an average of 1.7 m and a 20 % increase in surface soil salinity under current irrigation practices. These findings highlight the unsustainability of current water management and emphasize the urgent need for measures, such as effective drainage systems, or cultivation of salt-tolerant crops to ensure sustainable agricultural development.